Comparative Evaluation of Lipid Profile, C-Reactive Protein and Paraoxonase-1 Activity in Dogs with Inflammatory Protein-Losing Enteropathy and Healthy Dogs - Paola Gianella; Federica Cagnasso; Alessia Giordano; Antonio Borrelli; Enrico Bottero; Barbara Bruno; Riccardo Ferriani; Franca Borella; Sara Meazzi; Donatella Scavone; Saverio Paltrinieri (Animals)
Chronic inflammation alters lipoprotein metabolism and causes changes in the serum concentrations of lipids, C-reactive protein (CRP), and paraoxonase-1 activity (PON-1), an enzyme that may act as a local detoxifier, antioxidant, and immunomodulator in the gastrointestinal tract. Scarce information is available in dogs with protein-losing enteropathy secondary to chronic enteropathy (iPLE). The first aim was to describe and compare the lipid profiles, CRP concentrations and PON-1 activities in healthy dogs and in dogs with iPLE. The second aim was to evaluate correlations among clinicopathological, histologic data and lipid profiles in dogs with iPLE. Serum samples from 51 iPLE and 40 healthy dogs were used to study albumin, total protein, CRP, PON-1 activity, cholesterol, triglycerides and lipoprotein classes. Serum concentrations of albumin, total protein, cholesterol, PON-1 activity, and high-density and very-low-density lipoproteins were lower in iPLE dogs compared to healthy controls, while those of triglycerides, low-density lipoproteins, chylomicrons and CRP were higher. Significant correlations between the lipid profile and the existing chronic enteropathy activity index were not found. High-density and low-density lipoproteins correlated with CRP and PON-1. Triglycerides were significantly higher in dogs with both inflammation and lymphangiectasia. The results need to be confirmed in further studies.